Analisis Kesalahan Siswa SMAS Eria Kelas XI dalam Menyelesaikan Soal Cerita Pemecahan Masalah Persamaan Kuadrat Berdasarkan Taksonomi Newman (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the errors made by eleventh-grade students of SMA Swasta Eria in solving word problems related to quadratic equations and quadratic function graphs using Newman’s error taxonomy. The research employed a descriptive qualitative method involving 25 students who were given essay-type tests to measure both conceptual understanding and problem-solving skills. Data were collected from students’ written answers and analyzed according to Newman’s stages, which include reading, comprehension, transformation, process skills, and encoding. The findings reveal that errors occurred across all stages, with transformation errors and encoding errors being the most dominant. These mistakes generally stemmed from students’ inability to extract key information into correct mathematical models, inaccuracies in arithmetic operations, and insufficient understanding of fundamental quadratic concepts and their graphical representations. The results highlight the importance of instructional approaches that emphasize conceptual understanding, varied practice problems, and proper mathematical notation. Regular application of Newman’s error analysis is expected to help teachers provide more targeted feedback and improve students’ problem-solving abilities.